Bilateral abducens nerve palsy in an infant case of fulminant acute disseminated encephalomyelitis: a case report - Yang, Zhiliang (BMC Ophthalmol, 2016)
BACKGROUND: Sixth (abducens) nerve palsy (ANP) is far less frequent in children and has not been reported as a sign of acute disseminated encephalomyelitis (ADEM). We present an infant case of ADEM with bilateral abducens nerve palsy (BANP). CASE PRESENTATION: We report one case of BANP in a 15-month-old boy of fulminant ADEM. The patient underwent physical examinations and brain MRI scan three times during about six months follow-up. The patient had BANP and developmental regression when he regained consciousness from a coma, and the signs had persisted for 6-months. CONCLUSIONS: BANP can be a symptom of ADEM.